Needs Analysis for the Development of Teaching Materials for Writing Speech Texts in Grade VIII of Junior High Schools/Islamic Junior High Schools - Dinil Arifah; Charlina Charlina; Hasnah Faizah (Universitas Cokroaminoto Palopo, 2026)
This study aims to analyze the needs for developing instructional materials for teaching speech text writing to eighth-grade students in junior high schools (SMP/MTs). It focuses on identifying the gaps between existing materials and the actual needs of teachers and students to support effective and contextual speech-writing instruction. A descriptive qualitative method was employed through classroom observation, questionnaires, and document analysis involving Indonesian language teachers and eighth-grade students at MTs Baituddin Petapahan. The findings reveal a significant gap between the availability and the necessity of instructional resources, with 90% of teachers and 78% of students indicating the need for specialized materials, while only 25% of schools provide them. Existing materials were considered inadequate in terms of varied examples, language clarity, step-by-step guidance, and interactive exercises. Moreover, 83% of students reported difficulty understanding the content, and 72% noted insufficient practice opportunities. Although the visual design was rated moderately attractive, the materials lacked contextual relevance and substantive quality. In conclusion, the development of innovative, context-based materials that are visually appealing, structured, and enriched with diverse exercises is urgently required to improve students’ speech-writing skills. This study contributes theoretically by enriching the body of research on needs analysis in writing instruction, particularly in the context of speech text writing at the junior high school level, and practically by providing empirical evidence that can serve as a foundation for developing contextual, model-based, and learner-centered teaching materials. Recommendations include creating model-based instructional resources that incorporate local cultural values, authentic examples, and interactive digital media to enhance student engagement and instructional effectiveness.